2008
DOI: 10.1007/s00267-008-9171-x
|View full text |Cite
|
Sign up to set email alerts
|

Linking Theory and Practice for Restoration of Step-Pool Streams

Abstract: Step-pools sequences are increasingly used to restore stream channels. This increase corresponds to significant advances in theory for step-pools in recent years. The need for step-pools in stream restoration arises as urban development encroaches into steep terrain in response to population pressures, as stream channels in lower-gradient areas require stabilization due to hydrological alterations associated with land-use changes, and as step-pools are recognized for their potential to enhance stream habitats.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 72 publications
3
60
0
Order By: Relevance
“…Their morphological features have inspired the design criteria for artificial check dam sequences in high-gradient streams stabilization (Lenzi, 2002;Wang and Yu, 2007;Chin et al, 2009;Wohl et al in Conesa-García and Lenzi, 2010). Furthermore, several studies (Abrahams et al, 1995;Zimmermann and Church, 2001; Lee and Ferguson, 2002) have shown that step-pool morphologies tend to maximize flow resistance, leading to minimum velocity and shear stress, which is the final cause of its stability.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
See 1 more Smart Citation
“…Their morphological features have inspired the design criteria for artificial check dam sequences in high-gradient streams stabilization (Lenzi, 2002;Wang and Yu, 2007;Chin et al, 2009;Wohl et al in Conesa-García and Lenzi, 2010). Furthermore, several studies (Abrahams et al, 1995;Zimmermann and Church, 2001; Lee and Ferguson, 2002) have shown that step-pool morphologies tend to maximize flow resistance, leading to minimum velocity and shear stress, which is the final cause of its stability.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…This is the common interval of gradient found in check dam interventions (Heede, 1978;Nameghi et al, 2008), flume experiments (Abrahams et al, 1995;Comiti et al, 2009) and step-pool systems (e.g. Zimmerman and Church, 2001;Chartrand et al, 2011); c. check dam effective height z between 0.5-1.5 m, typical of control structures in agricultural areas (Heede, 1978;Nyssen et al, 2004;Nameghi et al, 2008); d. channel roughness ranging from 0.03 to 0.06, from clean and straight to weedy winding channels (Chow et al, 1994).…”
Section: Description Of the Modelmentioning
confidence: 99%
“…Where appropriate, sediment storage from incised streams could also be promoted with check dams (Geyik, 1986) and stone weirs (Shields et al, 1995), or more natural analogs using large wood (Shields et al, 2003), beaver dams (Pollack et al, 2014), and Native American techniques (Norton et al, 2002). In the Arroyo Mocho watershed, initial strategies to reduce erosion from incised channels include construction of a step pool channel (Chin et al, 2009), sediment retention ponds, and earthen check dams that also serve as cattle ponds (Bigelow et al, 2012a). In addition to sediment supply and sediment storage potential, practitioners should also consider the causes, current evolutionary stage, and history of channel incision within the watershed when determining the location of restoration projects to promote sediment storage (Schumm, 1999).…”
Section: Prioritize Areas For Sediment Storagementioning
confidence: 99%
“…These morphological units are able to almost maximize the energy losses due to the high flow resistance they generate [Whittaker and Jaeggi, 1982;Abrahams et al, 1995]. The analogies between step-pool/rapid sequences and engineered structures [e.g., consolidation check dams, bed sills, grade control structures, and ramps] have motivated investigations of naturally steep channels [Chin et al, 2009]. Steps contribute to the reduction of the mean energy slope mainly through the vertical flow drop that promotes a tumbling flow regime [Peterson and Mohanty, 1960] with a critical or supercritical jet flow over the step lip and subcritical dissipative flow in the pool [Zimmermann and Church, 2001;Wohl and Thompson, 2000].…”
Section: Introductionmentioning
confidence: 99%